Preference structures, choice functions and their logical form - Rodríguez-Galiano, María Isabel (2002)
Binary relations and choice functions are two different tools for describing DM preferences on a finite set of alternatives. Normal choice functions are the link between these two tools. These choice functions are easily identified using the logical form. In this paper, we analyse normal choice functions from the viewpoint of their logical form.